2017
DOI: 10.1038/srep41425
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dark foldable proteome by considering hydrophobic amino acids topology

Abstract: The protein universe corresponds to the set of all proteins found in all organisms. A way to explore it is by taking into account the domain content of the proteins. However, some part of sequences and many entire sequences remain un-annotated despite a converging number of domain families. The un-annotated part of the protein universe is referred to as the dark proteome and remains poorly characterized. In this study, we quantify the amount of foldable domains within the dark proteome by using the hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 64 publications
(113 reference statements)
3
35
0
Order By: Relevance
“…The focus of this study however, was the Homo Sapiens and other model organisms where it can be concluded that the amount of dark proteome present in them is still high, whereas in higher eukaryotes like mouse and human, it is around 50%. The results presented above are consistent with previous works (6,23), since Arabidopsis dark proteins are mainly located in extracellular space, cellular membrane and endoplasmic reticulum membranes. C. Elegans dark proteins are present again in cell membrane where they are secreted.…”
Section: Discussionsupporting
confidence: 93%
“…The focus of this study however, was the Homo Sapiens and other model organisms where it can be concluded that the amount of dark proteome present in them is still high, whereas in higher eukaryotes like mouse and human, it is around 50%. The results presented above are consistent with previous works (6,23), since Arabidopsis dark proteins are mainly located in extracellular space, cellular membrane and endoplasmic reticulum membranes. C. Elegans dark proteins are present again in cell membrane where they are secreted.…”
Section: Discussionsupporting
confidence: 93%
“…It can be observed that novel orphHCA domains show an overall higher fraction of disorder than novel Pfam domains, which is in agreement with a recent study showing that unannotated protein domains have a high disorder content [75]. 'New' domains that can be found in Pfam MDA (i.e.…”
Section: Structural Propertiessupporting
confidence: 90%
“…By contrast, regions lacking HCs or possessing only small and/or scarcely distributed HCs generally correspond to fully disordered sequences and/or flexible linkers. These features that can be deduced from HCA have been supported in a quantitative way by developing a tool, called SEG‐HCA, allowing to automatically delineate regions with high density in HCs (foldable regions) . The relevance of such approach has been supported by considering the coverage of domain and structure databases by the SEG‐HCA predictions .…”
Section: Hca and The Delineation Of Foldable Regionsmentioning
confidence: 99%